Prevalence of a second canal in the mesiobuccal root of permanent maxillary first molars from an Indonesian population - Harry H. Peeters (Nihon University, 2011)
A sample of 308 extracted human permanent maxillary first molars from an Indonesian population was randomly selected. A rhomboid access cavity was made in all teeth in anticipation of identifying a second mesiobuccal canal (MB2). Ultrasonic tips were used to open the subpulpal groove to locate the second canal in the mesiobuccal root. Dentin was carefully removed from the trifurcation area at the expense of the mesial wall. If a second canal was located, a 0.8 C+ file was inserted into it until the file reached the apex. The prevalence of a second canal in the mesiobuccal root of the permanent maxillary first molar was 68.5% (95% CI: 63.1%-73.4%) in this population. Sections of the mesial root showed that the MB2 was a separate canal in 52.6% of the sample and a joined canal in 47.4%. The mean (SD) distance between MB1 and MB2 was 1.55 (0.66) mm. The data obtained from this study provide theoretical and experimental evidence to aid in the clinical management of the MB2 canal and may increase the success rate for root canal treatment of the maxillary first MOLAR.